Talaromyces marneffei laccase modifies THP-1 macrophage responses. Issue 6 (17th August 2016) - Sapmak, Ariya; Kaewmalakul, Jutikul; Nosanchuk, Joshua D.; Vanittanakom, Nongnuch; Andrianopoulos, Alex; Pruksaphon, Kritsada; Youngchim, Sirida
ABSTRACT: Talaromyces (Penicillium) marneffei is an emerging opportunistic pathogen associated with HIV infection, particularly in Southeast Asia and southern China. The rapid uptake and killing of T. marneffei conidia by phagocytic cells along with the effective induction of an inflammatory response by the host is essential for disease control. T. marneffei produces a number of different laccases linked to fungal virulence. To understand the role of the various laccases in T. marneffei, laccase-encoding genes were investigated. Targeted single, double and triple gene deletions of laccases encoding lacA, lacB, and lacC showed no significant phenotypic effects suggesting redundancy of function. When a fourth laccase-encoding gene, pbrB, was deleted in the Δ lacA Δ lacB Δ lacC background, the quadruple mutant displayed delayed conidiation and the conidia were more sensitive to H2 O2, sodium dodecyl sulfate (SDS), and antifungal agents than wild-type and other transformants. Conidia of the quadruple mutant showed marked differences in their interaction with the human monocyte cell line, THP-1 such that phagocytosis was significantly higher when compared with the wild-type at one and 2 hours of incubation while the phagocytic index was significantly different from 15 to 120 minutes. In addition, killing of the quadruple mutant by THP-1 cells was more efficient at 2 and 4 hours of incubation. The levels of the proinflammatory cytokines TNF-α, IL-1β and IL-6 from THP-1 cells infected with the quadruple mutant were also significantly increased in comparison with wild-type. The results demonstrate that production of laccases by T. marneffei actually promotes the pathogen's resistance to innate host defenses.